1977
DOI: 10.1007/bf02615099
|View full text |Cite
|
Sign up to set email alerts
|

Fish cell culture: Characteristics of a cell line from the silver perch,Bairdiella chrysura

Abstract: A cell designated SP-1 was established from tissue of the silver perch, Bairdiella chrysura. Cells were fibroblast-like and grew best at 26 degrees C in Leibovitz medium (L-15) containing 15% fetal bovine serum and 0.150 M sodium chloride. Passage 1 to passage 9 SP-1 cells contained a chromosome number of 48; at passages 27 and 50 the modal numbers were 51 and 54, respectively. Confirmation of the origin of SP-1 cells was made by the cytotoxic antibody dye-exclusion test. This cell line supported the growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Through investigation of the karyotype of BmN cells, Pu et al, (2003) found that normal diploid cells (2n= 56) accounted for only 2.11% of total cells with great variation in chromosome number and with extreme heteroploidy and polyploidy. Wharton et al, (1977) suggested that animal cell lines may gain the ability to divide infinitely in culture accompanied by changes in karyotype. The 30th generation of the BmE-SWU2 cell line had 89.8%, diploid cell lines with minimal variations in chromosome number in the remaining cells.…”
Section: Discussionmentioning
confidence: 98%
“…Through investigation of the karyotype of BmN cells, Pu et al, (2003) found that normal diploid cells (2n= 56) accounted for only 2.11% of total cells with great variation in chromosome number and with extreme heteroploidy and polyploidy. Wharton et al, (1977) suggested that animal cell lines may gain the ability to divide infinitely in culture accompanied by changes in karyotype. The 30th generation of the BmE-SWU2 cell line had 89.8%, diploid cell lines with minimal variations in chromosome number in the remaining cells.…”
Section: Discussionmentioning
confidence: 98%
“…Ultrastructural investigation of infections in the heart of the silver perch demonstrated infections similar to those in the skin in the epicardium, trabecular spaces, and sub-endocardium, but not in the adjacent myocardial cells. Wharton et al (1977) established a fibroblast-like cell line from the swim bladder of the silver perch in which growth of the lymphocystis virus was supported but not of other viruses from fishes and mammals. They did not observe formation of the hyaline capsule in vitro, although frozen virus from their cell lines did produce tumor cells in vivo that contained this structure.…”
Section: Viralmentioning
confidence: 99%
“…Lymphocystis disease virus (LCDV) was firstly isolated from Japanese flounder, Paralichthys olivaceus (Temminck & Schlegel, 1846) (Sun, Hong, Zhang, Zhang & Wang ) and could infect other cell lines of marine fish species (Wharton, Ellender, Middlebrooks, Stocks, Lawler & Howse ; Chang, Ngoh, Kueh, Qin, Chen, Lam & Sin ; Sun, Qu & Zhang ; Lv, Wang, Li, Guo, Zhang, Bao & Zhou ), including four cell lines from half‐smooth tongue sole in our lab, which were the embryo (FEC) (Sha, Ren, Wang, Wang & Chen ), the heart (CSH) (Wang, Wang, Sha & Chen ), the testis (CGTC) (Zhang, Wang, Yang, Liu, Wang & Chen ) and the head‐kidney (TSHKC) (Zheng, Wang, Xie, Sha & Chen ). Among them, CSH was derived from the heart of the male individual.…”
Section: Introductionmentioning
confidence: 99%